Pengurangan Limbah Minyak Jelantah dengan Pelatihan Pembuatan Sabun Cuci Cair Ekonomis di Kampung Sawah, Bogor - Awwalunisa Aliya Kusuma (Patria : Jurnal Pengabdian Kepada Masyarakat, 2021)
Used Cooking Oil has a negative impact if it is dumped carelessly into the environment and has a positive impact if one of them is used is soap. In this study, corn cobs were used. This soap-making dedication activity aims to provide knowledge to the public regarding the economic potential of used cooking oil waste and corn cobs, skills training for the community regarding the processing of used cooking oil and corn cobs as laundry soap. The method is carried out in two stages: (a) Making soap with used cooking oil and corn cobs. Soap making is done using KOH as a reactant and fragrance to provide an attractive soap product. (b) Training activities for the community. Before and after training measured participants knowledge and attitudes with the questionnaire. The training activities were carried out in Kampung Sawah RW 06, attended by 16 participants. The Data analyzed univariate to see the characteristics of respondents and bivariate with a postwar test to assess the increase in knowledge and test Mc Nemar to assess the change in attitudes. There were increasing knowledge from an average of 3,52 to 4,08 (P = 0,004). Attitude changes also occurred before the training of positive attitudes as much as 43% to 94% after training (P = 0,021). The increased knowledge and attitudes that are statistic significan are expected to increase the increase in good behaviour in the processing of household waste, especially processing the waste oil and corn cobs.